2006
DOI: 10.1097/01.tp.0000197556.83675.a6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated HDL Cholesterol is Functionally Ineffective in Cardiac Transplant Recipients: Evidence for Impaired Reverse Cholesterol Transport

Abstract: Hyperalphalipoproteinaemia in cardiac transplant recipients is associated with the formation of partially dysfunctional HDL. We conclude that high levels of HDL may not confer cardioprotection in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…24 No difference in HDL size distribution was found between the groups or between pre-and postinfusion plasma samples (data not shown).…”
Section: Cholesterol Effluxmentioning
confidence: 97%
“…24 No difference in HDL size distribution was found between the groups or between pre-and postinfusion plasma samples (data not shown).…”
Section: Cholesterol Effluxmentioning
confidence: 97%
“…This might be of physiopathological relevance in the initial steps of atherogenesis, in which monocytes are arrested on the surface of endothelial cells. Recently, it was shown that hyperalphalipoproteinemia in cardiac transplant recipients is associated with the formation of partially dysfunctional HDL (46). Other studies showed that average HDL size and CE content increase as a result of low CETP activity (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Dysfunctional HDL in cardiovascular disease is not limited to CAD and acute coronary syndrome (ACS). Also in other cardiovascular diseases, such as heart failure, 42 ischaemic cardiomyopathy, 43 heart transplantion, 44,45 as well as in many conditions that are known to increase cardiovascular risk such as diabetes, CKD, acute and chronic inflammatory diseases, or familial hypercholesterolemia, [46][47][48] HDL has been found to lose its atheroprotective characteristics.…”
Section: Dysfunctional Hdl In Cardiovascular Diseasementioning
confidence: 99%